Current issues of pedagogy and psychology - Pronin A. Y., Konoplyansky D. A., Egorova G. V., Ryspaeva C. K., Ivanovskaia E. A., Orekhova S. E., Sivak O. A., Shevtsova A. V., Vinogradova I. A., Liakhova E. G., Khotuliova O. V., Medvedeva N. V., Novoselov K. A., Osipova A. A., Grigorev E. N., Khaibullin A. R., Fakhretdinova G. F., Zagrevskii V. I., Lavshuk D. A., Klochkov A. V., Sitdikova G. R., Malakhova L. A., Serova Z. N., Aleksandrov S. G., Satybaldieva R. A., Glotova G. A., Shipilova E. S., Koreneva A. V., Prisakaru E. I., Kazkanova C. T., Mukambetova G. B., Kazkanova C. T., Spiridonov E. A., Vasileva I. S., Shvaikina N. S., Pavlenko S. A., Akhmadeeva E. V., Pavlenko S. A., Zaluzhnaia M. V., Lavrentev M. V., Sulimin A. N., Khasin V. V., Churkina A. S. (Current issues of pedagogy and psychology, 2025)
the chapter actualizes the need to adjust the modern educational process in connection with the requirements of the time, the needs of students, representatives of the real sector of the economy. Experimental data are provided, reflecting the level of formation of digital competencies of higher education teachers. Methods and methods of their diagnostics, completion are discussed, digital solutions for achieving this are proposed. Algorithms for organizing the educational process using traditional, distance, electronic and blended learning are provided. Conclusions are made and recommendations are offered.
Keywords: инновации; innovations; competencies; цифровизация образовательного процесса; digitalization of the educational process; реальный сектор экономики; кометенции; real sector of the economy